Return on Equity dan Cumulative Abnormal Return Pada Perusahaan Perbankan - Ningrum, Rosmanita Kusuma; Usman, Usman (JURNAL ILMIAH MANAJEMEN & BISNIS, 2024)
Purpose – This research examines the influence of Return on Equity on Cumulative Abnormal Return with Sustainability Disclosure as a moderating variable in banking companies listed on the Indonesia Stock Exchange 2019-2023.Methodology – This research uses quantitative methods, using panel data analysis processed through EVIEWS 12. Seven companies were selected as research samples based on criteria, namely Bank Central Asia, Bank Negara Indonesia, Bank Rakyat Indonesia, Bank Danamon Indonesia, Bank Pembangunan Daerah Jawa Timur, Bank CIMB Niaga, and Bank Mega.  Findings – The findings reveal that Return on Equity has a negative, insignificant effect on Cumulative Abnormal Return, and Sustainability Disclosure strengthens the influence of Return on Equity on Cumulative Abnormal Return.Originality/Novelty – This research model uses Sustainability Disclosure as a moderating variable on Return on Equity on Cumulative Abnormal Return in banking companies. Given the strategic role and special regulation of banking in sustainable development through its intermediary function. Implications – This research provides a more comprehensive understanding of how investors respond to banking companies' Return on Equity and Cumulative Abnormal Return and how Sustainability Disclosure can strengthen or weaken Return on Equity on Cumulative Abnormal Return.